2022
DOI: 10.3390/en15124248
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Generators as an Alternative Energy Source in Shipboard Microgrids

Abstract: In recent years, the usage potential of alternative energy sources has been gaining importance to increase the efficiency of ships within the scope of the obligations brought by international maritime regulations. The possibility of using alternative energy sources such as solar energy, wind energy, fuel cells, and waste heat recovery technologies on ships has been evaluated in the literature. Today, ships also have waste heat recovery systems as standard equipment for this purpose, and this method is suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…However, due to delays in the delivery time, slow steaming may lead to increased logistic costs or increased CO 2 emission levels in comparison to land transportation [8]. Other measures for CO 2 reductions in shipping include the use of alternative fuels such as LNG, renewable energy sources (such as kites and solar cells), and waste heat recovery for power generation [1,9,11,12]. Eide et al [2] analyzed the cost-effectiveness of several technical and operational measures for reducing CO 2 emissions from shipping for selected ships and found that these measures were viable and should be pursued.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to delays in the delivery time, slow steaming may lead to increased logistic costs or increased CO 2 emission levels in comparison to land transportation [8]. Other measures for CO 2 reductions in shipping include the use of alternative fuels such as LNG, renewable energy sources (such as kites and solar cells), and waste heat recovery for power generation [1,9,11,12]. Eide et al [2] analyzed the cost-effectiveness of several technical and operational measures for reducing CO 2 emissions from shipping for selected ships and found that these measures were viable and should be pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies and techniques exist to increase heat flow to TEGs, including micro-and mini-channel heat sinks, two-phase flow systems, static mixers and porous media, the latter of which have been shown to be effective in waste heat recovery [15][16][17]. In the case of waste heat thermoelectric generators, there have been many conceptual designs of a power conversion system which are potentially capable of obtaining application in this area [18][19][20][21][22][23]. Other studies involving heat transfer from a fluid carrier to thermoelectric modules for thermal-to-electrical energy conversion have focused on porous media combustion and thermoelectric generation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, some selected papers are highlighted which address various transport sectors and applications such as Heavy-Duty Vehicles (HDV) [1,2], maritime transport [3,4], and even fuel cells [5]. A brief summary of each paper is given below.…”
mentioning
confidence: 99%
“…Exhaust gases from maritime transport also share potential energy extraction similar to that of HDVs. Uyanık et al [3] extract this potential with TEGs by identifying potential usage areas. This would ultimately increase the overall efficiency of the ship.…”
mentioning
confidence: 99%
See 1 more Smart Citation